The Influence of Pulsed Electron Beam Treatment on Properties of PLLA Nonwoven Materials Produced by Solution Blow Spinning; BioNanoScience; Vol. 8, iss. 1 - Kudryavtseva V. L. Valeriya Lvovna; Bolbasov E. N. Evgeny Nikolaevich; Ponomarev D. V. Denis Vladimirovich; Remnev (Remnyov) G. E. Gennady Efimovich; Tverdokhlebov S. I. Sergei Ivanovich (2018, 2018)
Title screen